1993
DOI: 10.3758/bf03211738
|View full text |Cite
|
Sign up to set email alerts
|

The indispensability of precollision kinematics in the visual perception of relative mass

Abstract: The visible kinematic pattern that occurs when objects collide contains information about the relative mass of the objects. Recently, Gilden and Proffitt (1989) have claimed that perceivers are limited to the use of simultaneous elemental cues and that therefore mass discrimination judgments are independent of whether the precollision epoch is visible or not. The present paper argues that their experimental results are irrelevant because crucial parameters were held constant, and that false conclusions were dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
108
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 20 publications
3
108
1
Order By: Relevance
“…In this situation, the basis of judgment will be predominately determined by an analysis ofspeeds. Runeson and Vedeler (1993) in their Experiment 1. Length of arrow represents speed, and all collisions are drawn to the same scale.…”
Section: Notes and Comment 709mentioning
confidence: 91%
See 3 more Smart Citations
“…In this situation, the basis of judgment will be predominately determined by an analysis ofspeeds. Runeson and Vedeler (1993) in their Experiment 1. Length of arrow represents speed, and all collisions are drawn to the same scale.…”
Section: Notes and Comment 709mentioning
confidence: 91%
“…The displacement of the point of subject equality in mass ratio toward large values of rnB/rnA is apparently due to the displacement of speed equality to rnB/rnA> 1.8. IfB is moving faster than A, subjects are Generalization of the Initial Conditions: Experiment 2 Experiment 2 was intended by Runeson and Vedeler (1993) to provide definitive support for their conjecture that observing the precollision kinematics is required for optimal judgment of mass ratio. As their method of occlusion in this experiment was to totally erase the precollision history of both objects, it is not surprising that they found that people were sometimes extremely inaccurate in their judgments in the occlusion conditions.…”
Section: Notes and Comment 709mentioning
confidence: 99%
See 2 more Smart Citations
“…determine specific kinematic (i.e., motion) patterns and that observers can determine the nature of an event from the resulting patterns of motion. The specific nature of the patterns that allowed recognition of the human motions was not described, although a potential source of information about relative mass in collisions was described and investigated (Runeson, /1983Runeson & Vedeler, 1993), with some ensuing controversy (Gilden & Proffitt, 1989, 1994Runeson, 1995). 1 Following an investigation of trajectories as information about lifted weight (Bingham, 1987b), proposed that trajectory forms are the information used to identify events.…”
mentioning
confidence: 99%